Teams Games Tournament Method Assisted Quizizz Media in Mufradat Learning for Students of The Islamic Education Management Program - Muhamad, Sahrul; Fitriani, Laily; Aziz, Abdul (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2023)
Arabic language learning methods that are less interesting tend to be boring, so the Teams Group Tournaments method assisted by Quizizz media can be a solution that can be applied. The aims of this research are: (1) to describe how to apply the Teams Group Tournaments method assisted by Quizizz media in learning Arabic vocabulary (2) to obtain information regarding student responses regarding the application of Teams Group Tournaments assisted by Quizizz media in learning mufradat. This research method is descriptive qualitative; data collection methods are observation and interview. The results of this research include: (1) there are strengths and weaknesses in implementing the Teams Games Tournament type cooperative learning model assisted by Quizizz in this research. The strength is that students become more enthusiastic, motivated, and easy to understand in learning Arabic, while the weakness is that the internet does not work, the class becomes noisy, and the projector LCD must be able to connect (2) the implementation of the Teams Group Tournaments method assisted by Quizizz media in learning  Arabic vocabulary makes students enthusiastic, happy, interested and easy to understand in learning Arabic, mainly Arabic vocabulary. The conclusions can be drawn, namely (1) the methods and media are very suitable for use in learning Arabic, (2) the level of student motivation in learning Arabic has increased, and (3) student satisfaction in the learning process that has been carried out has been achieved.